Application of fixed point results in the setting of F-contraction and simulation function in the setting of bipolar metric space - Gunaseelan Mani; Rajagopalan Ramaswamy; Arul Joseph Gnanaprakasam; Vuk Stojiljković; Zaid. M. Fadail; Stojan Radenović (AIMS Mathematics, 2023)
In the present work, simulation function is applied to establish fixed point results of F-contraction in the setting of Bi-polar metric space. Our results are extensions or generalizations of results proved in the literature. The derived results are substantiated with suitable examples and an application to find the solution to the integral equation.